Strategies for engineering communication - Stevenson, Susan; Whitmore, Steven (New York : Wiley, 2002)
"Strategies for Engineering Communication will help you master the skills needed to successfully communicate in situations commonly encountered by engineers. Throughout the text, you'll find flexible strategies for researching, drafting, and revising documents and speeches, for working individually and on teams, and for meeting the challenges of the many audiences, purposes, and contexts encountered at school and at work.
Numerous exercises and examples provide opportunities for you to examine your own writing and the writing of other engineers."--BOOK JACKET.
1. Planning and Inventing Strategies -- 2. Drafting and Revising Strategies -- 3. Rhetorical Strategies -- 4. Strategic for Teamwork and Workplace Communication -- 5. Oral Presentation Strategies -- 6. Stylistic Strategies -- 7. Format Strategies -- 8. Document Strategies and Sample Documentation.
Includes index.
Keywords: Communication in engineering